389 Sentinel node mapping with indocyanine green (ICG): initial analysis of prospective study. (18th September 2019) - Di Guilmi, J; Darin, MC; Monjo, I; Garcia Zeman, M; Maya, GA
Abstract : Objectives: To report initial experience in Argentina using a local production ICG. Evaluating detection rates, incidence of nodal metastasis and adverse effects. Methods: Prospective non randomized single centre study that included patients with endometrial and cervical cancer (Surgical stages). The protocol and the inform consent were inscribed in Health National Research Register (RENIS). 1, 25 mg/ml cervical injection of ICG (Laboratorio Bacon, Argentina) approved by ANMAT (National Administratios of Drugs, Food an Technology) for use in this protocol. Karl Storz Image 1 S laparoscopic system was used and the technique was standardized by protocol. Results: 51 patients were included between july 2017-march 2019. 18 had low risk endometrial carcinoma and 17 high risk. in the 1st group we only performed SLN biopsy. In the high-risk group, we performed SNL plus lymphadenectomy. 16 patients had cervical cancer. At least one SLN was found in 98% (50/51) for ICG. Bilateral detection rate was 88% (45/51) and most frequent localization was obturator basin. No serious adverse affect was reported. Incidence of macrometastases was 19% (10/51), micrometastases 5, 8% (3/51) and ITC 1, 9% (1/51). No false negative SLN was found. Conclusions: ICG does not have approval in Argentina for any medical uses. This issue is frequent in regional countries in which infrared technology is available but ICG is not approved by local regulations. In this preliminary analysis using ICG in pharmacological test phase we found high bilateral detection, no false negative and no adverse effects in relation of ICG injection. This protocol is open recruiting patients.